Cryogenic Thermomechanical Compressor - Simonenko Iu.M.; Chygrin A.A.; Kostenko Ye.V. (Problems of the Regional Energetics)
The purpose of this work is to create a compact supercharger to provide circulation of protective gas medium in a closed circuit. It was proposed to use a thermomechanical compressor to achieve this purpose. The operating principle of such devices is to change cyclically the temperature of the working medium in contact with warm and cold sources. Heating and cooling are carried out sequentially, pushing a part of gas through the regenerator by means of a displacer. The energy consumption for piston displacement is lower by an order of magnitude than that in conventional compressors. This makes it possible to use a seamless displacer movement mechanism. There can be two designs, both with one of the heat carriers close to ambient temperature. In a high-temperature thermomechanical compressor, the temperature is usually does not exceed 800 K. In the second type compressor, by reducing the absolute temperature of the cold "source" it is possible to achieve a high degree of compression at a relatively small temperature difference. The most significant result of the work is the design of the small-sized thermos-compressor that ensures a moderate degree of gas compression. The significance of the achieved results is shown in the compactness and tightness of the prototype for the use as an alternative to traditional machines in the field of inert gases production. The proposed technical solutions were tested during bench tests of the thermomechanical compressor. The experimental dependences were obtained of the flow rate characteristics on temperature mode, discharge pressure and cycle period.